2017
DOI: 10.1111/jnp.12127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cognitive impairment on prosodic parameters of speech production planning in multiple sclerosis

Abstract: Cognitive impairment (CI) affects 40-65% of patients with multiple sclerosis (MS). CI can have a negative impact on a patient's everyday activities, such as engaging in conversations. Speech production planning ability is crucial for successful verbal interactions and thus for preserving social and occupational skills. This study investigates the effect of cognitive-linguistic demand and CI on speech production planning in MS, as reflected in speech prosody. A secondary aim is to explore the clinical potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…Similar changes in temporal features of speech have been observed in other neurodegenerative diseases, e.g., mild cognitive impairment (Tóth et al 2018), Alzheimer's disease (Hoffmann et al, 2010;Meilán et al, 2014;Weiner, Neubecker, Mary, & Hynan, 2008), Parkinson's disease (Rektorova et al, 2016;Tjaden & Wilding, 2011), and Huntington's disease (Azambuja et al, 2012). Temporal characteristics of speech in MS are less described issues (DeLooze et al, 2017;Feenaugthy et al, 2013;Rodgers, Tjaden, Feenaughty, Weinstock-Guttman, & Benedict, 2013;Tjaden & Wilding, 2011).…”
Section: Temporal Features Of Speech In Mssupporting
confidence: 56%
See 2 more Smart Citations
“…Similar changes in temporal features of speech have been observed in other neurodegenerative diseases, e.g., mild cognitive impairment (Tóth et al 2018), Alzheimer's disease (Hoffmann et al, 2010;Meilán et al, 2014;Weiner, Neubecker, Mary, & Hynan, 2008), Parkinson's disease (Rektorova et al, 2016;Tjaden & Wilding, 2011), and Huntington's disease (Azambuja et al, 2012). Temporal characteristics of speech in MS are less described issues (DeLooze et al, 2017;Feenaugthy et al, 2013;Rodgers, Tjaden, Feenaughty, Weinstock-Guttman, & Benedict, 2013;Tjaden & Wilding, 2011).…”
Section: Temporal Features Of Speech In Mssupporting
confidence: 56%
“…The higher cognitive and linguistic demand and the time-limited or time-measured tasks require higher mental effort which might cause slower speech rate as well as more and longer silent and filled pauses (Arnett et al, 2008;DeLooze et al, 2017;Swets, Jacovina, & Gerrig, 2013). DeLooze et al (2017) found that MS patients with cognitive impairments produced more dysfluencies, slower speech rate, more silent pauses compared to MS patients without cognitive impairments. Feenaugthy et al (2013) measured slower speech rate and faster articulation rate, longer pauses and increased pause frequency both in cognitively impaired and non-impaired MS patients.…”
Section: Temporal Features Of Speech In Msmentioning
confidence: 99%
See 1 more Smart Citation
“…Pause time has been interpreted to reflect cognitive-linguistic planning demands (Feenaughty et al, 2013;De Looze et al, 2017;Svindt, Bona, & Hoffmann, 2020) or the demand to generate an internal motor plan free of linguistic context required for spontaneous speech (Sidtis & Sidtis, 2017). Thus, it could be speculated that speakers in the MSDYS þ CI group demonstrated significantly longer silent pauses to allow more time for language formulation or to generate an internal motor plan for the spontaneous speech task, as an external printed script or verbal model of the desired speech output was not provided.…”
Section: Speech Timing Measuresmentioning
confidence: 99%
“…With disease progression, swallowing problems can ultimately endanger patients 'lives. Interrupted speech, inability to make sentences, slowing or altering speech and swallowing disorder may be other MS symptoms [7].…”
Section: Respiratory Speech and Swallowing Disordersmentioning
confidence: 99%